Trabalho informal dos catadores de materiais recicláveis: relações de exploração e subordinação ao capital e Estado - Melo, Josimery Amaro de (2010)
Because of the structural changes occurred in the 1970s, the work, which is the source of revenue and sustainment of society and also of the capitalist rise was becoming fragile. By determinations of the own system, which after the crisis does not permit that all workers reproduce themselves anymore, having the laborite guarantees and rights, acquisitions of class struggle and concession of State, especially in the period known as the thirty glorious years, which was derived from a pact between Fordism and Keynesianism. The own logic of the system provoked the crises of capitalism and its way of management of the industrial production, the Fordism/Taylorism. This one was based on the large-scale production and it was gradually substituted by the lean production, which has brought the outsourcing, the production exteriorization and the informal work phenomena. The informal work or the new informality emerged from the productive restructuration marks the current stage of the global capitalism, because workers have been expelled from the formal labor market and they have been incorporated to the production, being exploited informally. Moreover, they have been developed works through associations and cooperatives, or even, they have sold their workforce through informal labor relations. In this case, the work is measured by the quantity of goods they produce, not by the time, what permits more exploitation of workers because they are responsible for their own work and do not have any labor law. It can e noted that the capital is always changing the means of production, promoting ways of exploitation which reduce the costs of production. In addition, there is the necessity to make products with shorter lifetime. In this sense, the decreasing utilization rate of the use value of goods acts, what enables the profitability of capital and expands clusters of garbage and disposables in the city dumps and streets of large and medium cities, originating another current phenomenon: the recycling. This phenomenon, far from having environmental objectives, reproduces the capitalist accumulation, because recyclables come to industries through the work of recyclable material collectors, which are submitted to the precariousness of work. The present research is about the organization of work of recyclable material collectors in the nuclei of selective collection of the municipality of João Pessoa, in order to apprehend the economical and political links, which consubstantiate the relationships between labor, capital and State. Based on the Marxist social theory, this investigation intends to realize one of the current expressions of the social question. Therefore, it is important to Social Work. This research confirms the hypothesis that associations are not autonomous: they are created and administrated by EMLUR, which have developed the income generation discourse based on the ideals of entrepreneurship of their associated, in the intention to serve the recycling industry. In reality, the informal collectors work with no guarantee of both the municipality and industry. As a counterpart, both maintain images of benefactors because they have offered survival conditions to these workers and also investing in a company with socio-environmental responsibility.